CASE REPORT: MANAGEMENT OF PHYSIOTHERAPY FOR GRADE III KELLGRENLAWRENCE RIGHT KNEE OSTEOARTHRITIS AT BHAYANGKARA HOSPITAL AWALOEDIN DJAMIN SEMARANG - Arifin, Akhmad Zaenal; Maqfiroh, Lailatul (Universitas Muhammadiyah Surakarta, 2021)
Background: Management of Physiotherapy for Osteoarthritis Dextra grade 3 Kellgren-Lawrence accompanied by tight hamstrings and decreased quadriceps muscle strength and decreased range of motion of the knee flexion joint. Objective: To report on the results of a physiotherapy program on Osteoarthritis Dextra grade 3 Kellgren-Lawrence with hamstring tightness and a decrease in quadriceps muscle strength and a decrease in the range of motion of the knee flexion joint. Methods: The patient is a 53-year-old woman with a primary diagnosis of Osteoarthritis Dextra grade 3 Kellgren-Lawrence accompanied by tight hamstrings and decreased quadriceps muscle strength and decreased range of motion of the knee joint for flexion. Physiotherapy was carried out 5 times with details of TENS in the area around the knee for 13 minutes, ultrasound of the hamstring tendon for 6 minutes, stretching of the hamstring as well as strengthening of the quadriceps muscle with stretching of the hamstrings tendon for 5 times. Therapy 2 times a week. Results: After 5 treatments, the results showed a decrease in pain from a score of 10 to 6, the level of difficulty from a score of 11 to 4 and the level of dependence from a value of 4 changed to a value of 3. The assessment was measured by the Jette scale. Conclusion: In this case there is a significant progress of changing the value on the Jette scale. This is probably because from the initial indication of OA, the patient immediately underwent a physiotherapy process.